2004
DOI: 10.1097/01.ju.0000132835.48647.23
|View full text |Cite
|
Sign up to set email alerts
|

The Male Perineal Sling: Comparison of Sling Materials

Abstract: Early results demonstrate that the male sling is a safe and efficacious treatment option for postprostatectomy urinary incontinence. This study demonstrates superior outcomes with the synthetic silicone mesh sling compared to the porcine dermal collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Recent reports for the perineal boneanchored sling have shown varying success rates. The group from Kaiser Permanente has shown that the sling procedure is much more successful when using synthetic rather than organic sling material [Dikranian et al, 2004]. Their success rates with synthetic sling are similar to the excellent success rate of the University of Arizona cohort.…”
Section: Discussionmentioning
confidence: 52%
“…Recent reports for the perineal boneanchored sling have shown varying success rates. The group from Kaiser Permanente has shown that the sling procedure is much more successful when using synthetic rather than organic sling material [Dikranian et al, 2004]. Their success rates with synthetic sling are similar to the excellent success rate of the University of Arizona cohort.…”
Section: Discussionmentioning
confidence: 52%
“…32 Evidence suggests that alloplastic material produces better continence results. 33 It remains mostly unknown what the mechanisms underlying restoration of continence are. Theoretically, tapes and slings could act by permanent urethral compression, a hammock type mechanism causing urethral compression only during abdominal pressure increase, elongation of the functional urethral length, or re-positioning of the proximal urethral into the abdominal cavity for increase of pressure transmission during physical activity.…”
Section: Slings-tapesmentioning
confidence: 99%
“…In the last few years, there has been revived interest in using male slings for postprostatectomy urinary incontinence [5][6][7][8] . A variety of sling materials were used in these studies, including cadaveric fascia, porcine dermis, polypropylene mesh, silicone mesh and synthetic material.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of surgical techniques have been described for the treatment of male stress incontinence [1][2][3][4][5][6][7][8] . In the last few years, there has been revived interest in using male slings for postprostatectomy urinary incontinence [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation